KETERAMPILAN DALAM MELAKUKAN PENGUKURAN BESARAN FISIS (LANGSUNG DAN TIDAK LANGSUNG) - Sayyadi, Muhammad (Fakultas Sains dan Teknologi, 2024)
The problem that often occurs in students who will do practicum is the lack of experience / prerequisite skills to do practicum. With this condition, it means that practice does not have innate skills from the previous level of education. The purpose of this study is to describe the basic skills of students of the Physics Education Study Program at PGRI Kanjuruhan University Malang in the Basic Physics Practicum course in using basic measuring instruments and skills in analyzing direct and indirect measurement results. Data collection was carried out using observation sheets and interviews. Purposive sampling is a technique carried out by determining samples with certain considerations. The length measurement skills obtained from 12 students were using a crossbar 64.3% skilled, using a caliper 55.95% skilled, using a screw micrometer 57.14% skilled. The mass measurement skills obtained are using a digital balance of 65.48% skilled, using a three-arm balance of 54.76% skilled. The time measurement skills obtained are using an analog stopwatch 63.10% skilled and using a digital stopwatch 60.71%. The indirect measurement skills obtained are that in measuring the volume of the copper cube 56.47% skillful, the density of the iron ball there are 53.57% skilled students.